Reversible Job-Switching Opportunities and Portfolio Selection - Shim, Gyoocheol; Koo, Jung Lim; Shin, Yong Hyun (Applied Mathematics and Optimization, 2018)
We study an optimal job-switching and consumption/investment problem of an infinitely-lived economic agent who exhibits constant relative risk aversion. We consider two kinds of jobs, one of which allows the agent to receive higher income but makes him suffer higher level of utility loss than the other. The job-switching opportunities are reversible in the sense that one can move from the current job to the other at any time. We provide the closed form solution for the optimal job-switching and consumption/investment policies by using the dynamic programming approach, and show various properties of the solution. We compare the optimal consumption/investment policies to those without job-switching opportunities. As a special case of our problem, we also compare the solution in the case where the agent has a reversible retirement option with that in the case where he has an irreversible retirement option.
Keywords: Closed form solutions; Constant relative risk aversion; Consumption; Consumption/investment; Disutility; Job switching; Optimal consumption; Portfolio selection; Consumption; Disutility; Labor income; Portfolio selection; Reversible job-switching